2009
DOI: 10.1177/000494410905300104
|View full text |Cite
|
Sign up to set email alerts
|

Policy, Practice and the ‘Revolving Classroom Door’: Examining the Relationship between Aboriginal Spatiality and the Mainstream Education System

Abstract: Indigenous academic outcomes are in many ways negotiated at the interface between student spatialities—including their residential patterns and choices—and the mainstream school system. The current model of education delivery rewards regular attendance at well-resourced schools. Conversely, sporadic interactions with under-resourced schools generally produce poor educational outcomes. This paper draws on qualitative case-study research in Yamatji country, Western Australia, to present a grounded analysis of th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
14
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 14 publications
1
14
0
Order By: Relevance
“…Since the HREOC inquiry in 2000, a growing number of boarding schools have made long-term commitments and undertaken significant efforts to better support Indigenous students from regional and remote communities (Australian Indigenous Education Foundation, [AIEF], 2015). However, concern still exists around the impact that having a child studying away from home has on Indigenous families (Mander & Fieldhouse, 2009; Prout, 2009; Stewart, 2015). At a policy level, the national Aboriginal and Torres Strait Islander Education Action Plan 2010–2014 (Ministerial Council for Education, Early Childhood Development and Youth Affairs, [MCEECDYA], 2011) and the Melbourne Declaration on Educational Goals for Young Australians (MCEECDYA, 2008), as well as more broadly the National Indigenous Reform Agreement – Closing the Gap (Council of Australian Governments, [COAG], 2011), collectively seek to encourage state and territory governments to improve school attendance and retention figures as well as academic outcomes and general access to education for Indigenous children living in regional and remote communities.…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Since the HREOC inquiry in 2000, a growing number of boarding schools have made long-term commitments and undertaken significant efforts to better support Indigenous students from regional and remote communities (Australian Indigenous Education Foundation, [AIEF], 2015). However, concern still exists around the impact that having a child studying away from home has on Indigenous families (Mander & Fieldhouse, 2009; Prout, 2009; Stewart, 2015). At a policy level, the national Aboriginal and Torres Strait Islander Education Action Plan 2010–2014 (Ministerial Council for Education, Early Childhood Development and Youth Affairs, [MCEECDYA], 2011) and the Melbourne Declaration on Educational Goals for Young Australians (MCEECDYA, 2008), as well as more broadly the National Indigenous Reform Agreement – Closing the Gap (Council of Australian Governments, [COAG], 2011), collectively seek to encourage state and territory governments to improve school attendance and retention figures as well as academic outcomes and general access to education for Indigenous children living in regional and remote communities.…”
mentioning
confidence: 99%
“…Centrelink figures in 2010 indicated that 793 Aboriginal students in WA received the Aboriginal and Torres Strait Islander Student Assistance Scheme (ABSTUDY) –– Schools Fees Allowance (Boarding) Supplement, so that they could attend a secondary boarding school away from home (A. Davila, personal communication, October 11, 2010). This suggests that each year many Aboriginal parents living in remote communities of WA are confronted by the highly challenging task of discerning between boarding schools that are not only unfamiliar but also distant from home, in an effort to access the best possible secondary education for their children (Prout, 2009) –– a circumstance according to Stewart (2015) that is unlikely to change in the near future. He asserts: State, Territory and Commonwealth education policy and subsequent resource allocation mean that it will not be possible for young Indigenous men and women to participate in a quality comprehensive secondary education in many of their home communities.…”
mentioning
confidence: 99%
“…Except for this peak in mobility among Indigenous youth, life-stage appears to shape the reasons for Indigenous temporary movement more than the frequency of such moves. For example, many Indigenous children are highly mobile, travelling with their families and guardians, or independently (Henry and Smith 2002;Prout 2009b;Sorin and Ilsote 2006). Other studies also describe older people as frequent movers (Birdsall 1988;Morphy 2007b;Smith 2002).…”
Section: The Demography Of Indigenous Temporary Mobilitymentioning
confidence: 99%
“…For example, attitude to school, relationships with teachers and peers, school culture and leadership, curriculum content and relevance, as well as teacher preparedness, expectations and pedagogy are habitual themes in this research (Beresford, Partington, & Gower, 2012). Parental employment and educational attainment (Zubrick et al, 2006), family mobility and wider community factors such as access to resources and services have also been investigated (Prout, 2008(Prout, , 2009.…”
Section: Introductionmentioning
confidence: 99%